Soldiers and Scholars: Evaluating Female Engagement Teams in the War in Afghanistan. Issue 1 (2nd January 2021) - Keohane, Jennifer; Jakes, Kelly
Abstract: The War in Afghanistan inaugurated a shifting gender climate among all levels of the U.S. military. Counterinsurgency demanded that soldiers attempt to win "hearts and minds" of local populations and sent women soldiers to engage Afghan women in newly created female engagement teams (FETs). Analyzing the effectiveness of these teams fell to women analysts. Writing in the advent of a softer form of military masculinity and an appreciation for women's role in war, analysts seized the opportunity to construct themselves as experts by centering gender in their critique of military strategy. However, the conditions that authorized their voices committed them to measuring the FETs by masculine standards of objectivity and rationality. Thus, while the analysts faulted the military for ignoring gender, they also delegitimized the FETs by accepting gendered ways of knowing that denigrated their service.